DEVELOPMENT OF THE TECHNICAL AND TECHNOLOGICAL POTENTIAL OF AGRICULTURAL ENTERPRISES AS A DIRECTION FOR ENSURING SUSTAINABILITY IN THE CONTEXT OF GLOBAL TRANSFORMATIONS - SHERSTIUK, Oleksandr; KHALIN, Stanislav (Herald of Khmelnytskyi National University. Economic sciences, 2025)
The article focuses on the study of the directions for developing the technical and technological potential of agricultural enterprises as a factor in ensuring stability in the context of global transformations.Increasing the importance of the principles of sustainable development, environmental safety, and the economic use of resources necessitates revising approaches to conducting agricultural activities.It has been established that in the modern conditions of global transformations, which are accompanied by climate change, geopolitical challenges, and economic instability, the stability of agricultural enterprises is determined not only by natural resources, but also by the level of development of their technical and technological potential. The modernization of the technical base, the introduction of digital technologies, the automation of production processes, the development of infrastructure, and the use of renewable energy sources form the basis of adaptive and competitive agricultural production.It has been determined that these directions enable an increase in the efficiency of resource use and a reduction of environmental impact, optimizing and adapting to rapid changes in the external environment. At the same time, investments in training and the implementation of sustainable development principles contribute to the long-term stability of enterprises.It is substantiated that approaches to strategic management in the agricultural sector are transforming, particularly by reorienting towards crisis planning, increasing adaptability in an unstable environment, responding promptly to threats, and actively seeking new sources of stability. The ability of agricultural enterprises to adapt flexibly to external challenges is becoming increasingly crucial not only for ensuring their current stability but also for fostering the potential for sustainable development in the long term, especially in the context of post-crisis economic changes.The development of technical and technological potential should be considered as a strategic tool for ensuring the economic, environmental, and social stability of the agricultural sector in the context of global challenges.
Keywords: agricultural enterprises; agricultural technologies; innovative capacity; competitive advantages; development; sustainability; technical and technological potential; transformation